Measurement of the properties of GaN layers using terahertz time‐domain spectroscopic ellipsometry. Issue 8 (17th July 2017) - Tachi, Kohei; Asagami, Shiho; Fujii, Takashi; Araki, Tsutomu; Nanishi, Yasushi; Nagashima, Takeshi; Iwamoto, Toshiyuki; Sato, Yukinori; Morita, Naotake; Sugie, Ryuichi; Kamiyama, Satoshi
Abstract : The electrical properties of an n‐type GaN wafer and epitaxial layer were evaluated using terahertz time‐domain spectroscopic ellipsometry (THz‐TDSE). The electrical properties, such as carrier density and mobility, were determined by fitting the reflective spectra of the sample using the Drude model. The measured properties of the GaN by THz‐TDSE are consistent with those obtained by conventional Hall methods. For the GaN epitaxial layer on sapphire substrates, the thickness was obtained by THz‐TDSE and compared with other measurements. THz‐TDSE has shown to be a suitable technique for evaluating the electrical properties of n‐type GaN materials non‐destructively and without contacts.